Building Participatory Networks for HIS in a Developing Country Context : A Case Study from India - Karen Hafsal (Department of Informatics, UNIVERSITY OF OSLO, 2006)
This thesis is drawn from an ongoing action research project, Health Information Systems Program (HISP) which aims at developing sustainable, computerised Health Information Systems (HIS) in developing countries in order to improve the quality of health service delivery and to create local action and analysis. The research in this thesis is conducted in Kerala in India, where the use of participatory practices is studied in a developing country perspective. Participatory Design is generally seen as a precondition of the development of successful systems. However, the PD tradition has been criticised for being outdated and incomplete. With basis in these critiques, this thesis addresses the need for a re-conceptualised PD which is more adaptable to the development of large and complex information infrastructures rather than single, locally-based systems. From this area of interest, the following research questions arose: i) How has PD been used in the HISP project in Kerala, and how has it been helpful? ii) What aspects of social, political and cultural context shapes participatory processes in a developing country context like that in Kerala, India? iii) How do participatory processes in contexts like India differ from those in Scandinavia? I have approached the problem domain using an action research approach and draw upon the theories of PD and Information Infrastructure (II). In order to carry out the research, a thorough understanding of the HIS in Kerala had to be obtained, and hence the II theory provided a functional socio-technical perspective to study the HIS. Further I use PD theory to understand the participatory processes used in Kerala and how this theory can be further improved to suit the complex contexts of HIS in developing countries. The main research contributions of this thesis are the building of participatory networks which involves networks of stakeholders both multi-sectoral and multi-leveled. Also the context-sensitivity of PD is emphasised and it is argued how the context of which the system is introduced highly influences the use of PD. Additionally, a need for shifting focus from PD techniques to the outputs of such processes is discussed, as well as the need to focus on structural as well as behavioural changes when conducting PD processes.